Unravelling the synergistic effects of arbuscular mycorrhizal fungi and vermicompost on improving plant growth,nutrient absorption, and secondary metabolite production in ginger (Zingiber officinale Rosc.) - Sarathambal, C.; Srinivasan, V.; Jeevalatha, A.; Sivaranjani, R.; Alagupalamuthirsolai, M.; Peeran, Mohammed Faisal; Mukesh Sankar, S.; George, Priya; Dilkush, Fathima (Frontiers in Sustainable Food Systems, 2024)
The present research explored the impact of varying concentrations of arbuscular mycorrhizal (AM) fungus inoculum and vermicompost on the growth, nutrient absorption, photosynthetic gas exchange, and quality paramters of ginger over a two-year period in field conditions. In this study, the combination of 50 g each of AM and vermicompost increased plant height, number of tillers, and rhizome yield compared to the control. However, higher dry biomass (61 g) was observed with the combination of 75 g of each amendment. As expected, the application of arbuscular mycorrhizae (AM) positively affects spore count and mycorrhizal dependency percentage ranging from 58 to 70.5 spores per 50 g substrate and 19-36% respectively. The combined use of vermicompost and AM led to a lower disease incidence of 10.5% in treatments with 25 g of each amendment and 10.1% in treatments with 50 g of each. Nutrient accumulations, particularly phosphorus (P), iron (Fe), and zinc (Zn), exhibited greater levels in ginger plants treated with vermicompost and arbuscular mycorrhizal (AM) inoculation, compared to uninoculated ginger rhizomes. The plants treated with AM and vermicompost increased the biomass accumulation by increasing the stomatal conductance and photosynthetic rate of leaves. AM and vermicompost improved ginger rhizome quality, increasing phenols by 37.8%, flavonoids by 35.7%, and essential oil by 29% compared to the control. The analysis revealed that the total flavonoid content was significantly higher in AMtreated samples compared to the control. However, the phenol content did not exhibit statistical significance across the treatments. Regarding essential oil (EO) content, our experiment highlighted that treatments with AM and vermicompost have consistently yielded higher EO content compared to other treatments. In contrast, there was no discernible trend in the fibre content with the application of AM and vermicompost amendments. PCA and correlation analyses revealed a positive influence on plant growth, nutrient absorption, and quality parameters, except for the incidence of diseases in ginger. Overall our study finds that the concurrent use of vermicompost and arbuscular mycorrhizae (AM) makes a substantial contribution to growth, nutrient uptake, photosynthetic, and quality parameters of ginger.